(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Gender attitudes and its factors continue to be debated in an era where gender equality remains a priority to countries in the world. Modernization theorists have assumed a predictable positive pattern of the influence of economic development on gender attitudes, thereby arguing that higher levels of economic development such as GDP per Capita, increases support for gender equality across countries. Whereas this has been proven in European and Western countries, it is difficult to generalize the results to African countries as the phenomenon is understudied on the continent. Using data from the 5th round of the Afrobarometer survey and multiple regression/multi-level analysis, this study investigated the influence of economic development, in addition to other socio-cultural factors, on gender attitudes in 34 African countries. The study revealed that a) among countries in Africa, economic development, in this case GDP per Capita, does not significantly influence attitudes towards gender equality; b) people’s ethnic background influences their attitudes towards gender equality; and c) Gender attitudes are strongly influenced by education, employment status and religious denomination.